Nutritional influences on inflammation and type 2 diabetes risk. - Browning, L; Jebb, SA (2006)
There is a clear role for inflammation in the development of type 2 diabetes and its associated co-morbidities. Circulating inflammatory markers such as C-reactive protein, sialic acid, and interleukin- 6 are all significant independent predictors of disease. A number of nutritional components are hypothesized to modulate inflammation, and hence impact on disease risk. The most extensively studied nutrients are the long-chain n-3 polyunsaturated fatty acids. However, evidence is also emerging with respect to whole grain or low glycemic index foods and antioxidant vitamins. Obesity, resulting from long-term dietary energy excess, is also strongly linked to raised inflammatory status and type 2 diabetes. To date, much of the evidence for the effect of nutrients or foods on disease risk has been based on epidemiological associations. However, the links among diet, inflammation, and type 2 diabetes are supported by some data from human dietary intervention trials and/or mechanistic studies in animals. Further research is required to quantify the precise role and refine the evidence base. However, the proposed "anti-inflammatory" strategies to tackle type 2 diabetes are broadly consistent with current public health nutrition guidelines: to achieve and maintain a healthy weight, to reduce saturated fat, to increase the proportion of less refined forms of carbohydrate, and to increase intake of fruits and vegetables.